2020
DOI: 10.31415/bjns.v3i2.101
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on Citrus aurantifolia essential oil: its phytochemistry and pharmacological aspects

Abstract: Citrus essential oil, commonly, known as lime oil, has been widely reported in traditional system of medicine. Industrially, oil is isolated by mainly by hydrodistillation from fruit and peel of Citrus aurantifolia, family, Rutaceae. Cultivation practice of citrus plants dates back for over 4000 years and are one of most valuable fruit crops in the world. In this review, we aim to summarise the phytochemical and biological properties of citrus oil. The literature was collected from various online resources suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
3
17
0
1
Order By: Relevance
“…Besides that, they also have oxygenated monoterpenes about 21%, and the rest are sesquiterpene compounds. This finding was supported by other studies which found differences in chemical profiles in the peel, leaves, and flowers of citrus species [4], [18].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Besides that, they also have oxygenated monoterpenes about 21%, and the rest are sesquiterpene compounds. This finding was supported by other studies which found differences in chemical profiles in the peel, leaves, and flowers of citrus species [4], [18].…”
Section: Discussionsupporting
confidence: 87%
“…The most popular types of citrus are Sweet oranges (Citrus sinensis Osbeck), Mandarins (Citrus reticulata Blanco), Grapefruits (Citrus paradisi Macfadyen), Lemons (Citrus limon Burmann), and Limes (Citrus aurantifolia Swingle). Flavonoids, limonoids, coumarins and furanocoumarins, sterols, essential oils (EO), organic acids, and alkaloids are among the many biologically active secondary metabolites found in members of this genus [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swingle ( Aracil and Green, 2019 ) and Morinda lucida Benth (Rubiaceae). Interestingly, available evidence indicates that these promising antimalarial plants additionally have the potential to tackle oxidative stress, regulate inflammatory response and stimulate the immune system to overcome complications observed in COVID-19 [ Level III ] ( Haudecoeur et al, 2018 ; Asante et al, 2019 ; Madzuki et al, 2019 ; Afolayan et al, 2020 ; Jain et al, 2020 ; Zibaee et al, 2020 ). Meanwhile, some of these reports lack quality and will require validation.…”
Section: Methodsmentioning
confidence: 99%
“…Swingle (Aracil and Green, 2019) and Morinda lucida Benth (Rubiaceae). Interestingly, available evidence indicates that these promising antimalarial plants additionally have the potential to tackle oxidative stress, regulate inflammatory response and stimulate the immune system to overcome complications observed in COVID-19 [Level III] (Haudecoeur et al, 2018;Asante et al, 2019;Madzuki et al, 2019;Afolayan et al, 2020;Jain et al, 2020;Zibaee et al, 2020). Meanwhile, some of these reports lack quality and will require validation.…”
Section: Therapeutic Convergence In the Use Of Antimalarial Plants Against Viral Infections In Africamentioning
confidence: 99%